Assessing the role of internal audit unit in the corporate governance – A case of Komfo Anokye Teaching Hospital - Hussein, Alhaji Iddrisu (2016)
A thesis submitted to School Business, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of Master of Business Administration (Accounting Option),